230 MITRAL STENOSIS AS A RARE PRESENTATION OF CARCINOID SYNDROME. Issue 1 (1st January 2007) - Dave, B.; Godkar, D.; Niranjan, S.; Lin, K.
Abstract : Background: Heart disease, although uncommon with carcinoid syndrome, may be seen in up to 60% of patients with metastatic carcinoid syndrome. Valvular disease is the most common pathologic feature, and tricuspid damage is found in 97% and pulmonary valve disease in 88, with 88% displaying insufficiency and 49% stenosis. Left-sided heart involvement is extremely rare, and in the presence of mitral valve involvement, one should think about extensive liver metastases, patent foramen ovale, or bronchial carcinoid syndrome. In the setting of bronchial carcinoid syndrome, the left-sided lesions on the mitral valve may be so extensive as to cause mitral stenosis. Case Report: We present a case of a 50-year-old woman who was being treated for bronchial asthma for 3 years and had not responded to treatment. In view of recurrent episodes of dyspnea, she was referred to us for a two-dimensional echocardiography, which showed marked thickening of the mitral valve leaflets and mitral stenosis. Bubble study failed to reveal shunt. Left-sided heart involvement with symptoms of wheezing and dyspnea prompted us to consider bronchial carcinoid syndrome as a differential diagnosis. Diagnosis was confirmed with a high 5-hydroxyndole acetic acid (5-HIAA) urinary excretion and the presence of a 1.5 cm left-sided endobronchial tumor on CT scan of the chest, later confirmed by biopsy as carcinoid tumor. The patient was referred to a tertiary center for resection of the tumor and mitral valvulotomy/replacement. Discussion: Right-sided valvular heart disease is a common complication of metastatic carcinoid tumors. On the contrary, left valve involvement is a rare finding. The distinctive carcinoid lesion consists of deposits of fibrous tissue devoid of elastic fibers known as carcinoid plaque. The deposits are found on the endocardial surface on the ventricular aspect of the tricuspid/mitral leaflets and on the arterial aspect of the pulmonary/aortic valve cusps. Once diagnosed, further course depends on the extent of metastases. Recent studies have shown that with good preoperative medical control of the carcinoid activity and meticulous anesthesia, the mortality may be as low as 20%, even with left-sided heart involvement.